Factor: 4a^2c^2 - (a^2-b^2+c^2)^2

### 1 Answer | Add Yours

The expression 4a^2c^2 - (a^2-b^2+c^2)^2 has to be factored.

4a^2c^2 - (a^2 - b^2 + c^2)^2

=> (2ac)^2 - (a^2 - b^2 + c^2)^2

=> (2ac - a^2 + b^2 - c^2)(2ac + a^2 - b^2 + c^2)

=> (b^2 - (a^2 - 2ac + c^2))((a^2 + 2ac + c^2) - b^2)

=> (b^2 - (a - c)^2)((a + c)^2 - b^2)

=> (b - a + c)(b + a - c)(a + b + c)(a - b + c)

**The factorized form of 4a^2c^2 - (a^2-b^2+c^2)^2 is (b - a + c)(b + a - c)(a + b + c)(a - b + c)**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes